2018
DOI: 10.1177/0891243218794865
|View full text |Cite
|
Sign up to set email alerts
|

Drag as a Resource: Trans* and Nonbinary Individuals in the Southeastern United States

Abstract: Through 32 in-depth surveys with drag kings, I ask how do trans*/nonbinary individuals find a way to make a home in the southeastern United states? I answer this by examining the use of drag kinging as a resource to explore gender identity and find resources for gender transition. This study adds to previous research on drag kinging by expanding beyond large cities and college towns to include a broader look at the southeast, where queer lives have often been rendered invisible. I highlight the importance of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These obstacles are even more pronounced in the Southeastern United States (Rogers , , Forthcoming). In the South, the LGBTQ community faces elevated stressors due to continued prejudice, discrimination, and oppression (Barton ; Baunach, Burgess, and Muse ; Bradford et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These obstacles are even more pronounced in the Southeastern United States (Rogers , , Forthcoming). In the South, the LGBTQ community faces elevated stressors due to continued prejudice, discrimination, and oppression (Barton ; Baunach, Burgess, and Muse ; Bradford et al.…”
Section: Introductionmentioning
confidence: 99%
“…() found that sourcing support from a social group or team may enhance mental health, as groups or teams provide a shared identity, language, and structure of accountability for member engagement. In a study of drag performers in the U.S. Southeast, Rogers () found that seeking support from a shared cultural community allows performers to locate information about access to services that are often hidden from dominant view or unavailable to the general public and demonstrates the responsibility that marginalized people often feel to offer support, in its many forms, to those struggling in their communities. In a study of trans people and medicalization, Johnson () found that sourcing support from the trans community may facilitate the acceptance of a marginalized identity, as it offers a community‐based counternarrative to hegemonic discourse.…”
Section: Introductionmentioning
confidence: 99%
“…Research about trans women and trans men has been prominent within the field of sociology since West and Zimmerman’s (1987) famous article “Doing Gender,” but research about nonbinary genders has historically remained sparse. This trend has begun to shift over the last few years, as evidenced by Gender & Society ’s recent publications that analyze nonbinary particularities (Garrison 2018; Rogers 2018; shuster 2017). Indeed, the sociology of gender has made strides more broadly toward acknowledging the gender diversity that exists beyond binary categories such as cis men, cis women, trans men, and trans women (Schilt and Lagos 2017).…”
mentioning
confidence: 99%
“…One early study on three diverse communities of transgender women argues that scholars must understand ethnocultural communities, including immigration status and community lifestyles, in order to study transgender health (Hwahng and Nuttbrock ). Networks of commonality, such as those in drag king networks, may be supportive resources for trans and non‐binary people in the south or other regions of increased transphobia (Rogers ). The importance of specificity of connection, particularly connecting on multiple demographics, was most important for TNB people of color in this study.…”
Section: Multiplicity Place and Communitymentioning
confidence: 99%